RANKING RUSSIAN UNIVERSITIES: HOW TO MEASURE? - Maria V. Seroshtan; Boris M. Vladimirskiy (Высшее образование в России, 2016)
The authors propose to use vector representation of university areas of activities for ranking universities. Two novel indices reflecting UN experts’ recommendations are introduced. Based on expert estimates, a priority vector of weights enables to represent the university activity.